Optimizing the availability of high frequency precision quenching machines through the overall equipment effectiveness approach at PT XYZ - Arif Nuryono; Yuri Delano Regent Montororing; Andika Risky Wijaya; Hibarkah Kurnia (LPPMPK- Universitas Muhammadiyah Cileungsi, 2026)
One of the Automotive companies that uses a High Frequency Precision Quenching (HFPQ) machine experiences a high downtime problem of 71.27%, which causes a low availability value of 80.10%, which is still below the world-class standard of 90%. so that production targets are not achieved optimally. This study aims to analyze the effectiveness level of the HFPQ machine and identify the factors causing low availability to increase the Overall Equipment Effectiveness (OEE) value. The research method uses an analytical integration approach with the OEE method, Six Big Losses (SBL) analysis, and other methods. The results show that the HPPQ machine's availability value before improvement was 80.10%, after improvement it increased by 92.25%, meaning an increase of 12.15%. The largest losses were caused by downtime losses and setup losses, totaling 37,640 minutes over a 6-month period. This condition resulted in availability being the dominant contributor to OEE losses, with a value of approximately 71.27%. Based on the proposed improvements, the availability increased by 92.25%, meaning an increase of 12.15%, while the OEE value improved from 70.39% to 86.07% or an increase of 15.68% after implementing maintenance improvements. This research is expected to provide a basis for improving the machine maintenance system in order to enhance the effectiveness and productivity of the company.